FUNCTIONS AND CONTRIBUTIONS OF SOCIOLOGY - Jannah, Miftahul (UNIVERSITAS PGRI TULUNGAGUNG, 2023)
The study of the function and contribution of the sociology of religion is very important to study in more depth. This is because these studies never stop being debated. The aim of this paper is to understand 3 things: First, the paradigm regarding the function and contribution of the sociology of religion. Second, the internal and external factors that influence the function and contribution of the sociology of religion. Third, the positive and negative implications of the function and contribution of the sociology of religion to the lives of religious communities. The method used is qualitative with a literature approach based on theory, while data is collected using methods and analyzed using techniques. The results found were 3 things: First, there are 3 forms of paradigm: (1). etymological meaning (language) (2). understanding terminology (terms) (3). characteristics/categories/classifications. Second, internally, there are 3 factors that influence the function and contribution of the sociology of religion: (1). urgency (2). genealogical (3). contribution. Externally, there are 3 factors that influence the function and contribution of the sociology of religion: (1). environmental/geographical (2). situation (3). condition. Third, there are 3 positive implications of the function and contribution of the sociology of religion to people's lives: (1). tolerance (2). moderation (3). solidarity. Meanwhile, there are 3 negative implications: (1). violence (2). radicalism and (3). politicization of religion The conclusion of this paper shows that the study of the function and contribution of the sociology of religion has several positive and negative views in social life.